2009
DOI: 10.1016/j.jcrs.2008.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate optimization of vision with bilateral nonaspheric multifocal intraocular lens implantation

Abstract: Intermediate optimization with slight myopia in 1 eye after bilateral implantation of the multifocal IOL offered consistent good vision at all ranges, indicating it a safe option for patients who require good vision at intermediate ranges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Vice versa, diffractive multifocal IOLs have been combined with mini-monovision strategies to increase visual function at intermediate distances. 17,20 Recently, trifocal diffractive IOLs have been proposed to increase intermediate visual acuity. 21 The introduction of diffractive multifocal IOLs with lower near additions yielded better results at intermediate distance without decreasing near and distance visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, diffractive multifocal IOLs have been combined with mini-monovision strategies to increase visual function at intermediate distances. 17,20 Recently, trifocal diffractive IOLs have been proposed to increase intermediate visual acuity. 21 The introduction of diffractive multifocal IOLs with lower near additions yielded better results at intermediate distance without decreasing near and distance visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Blaylock et al [ 10 ] reported that after the implantation of a Restor +4D in 37 eyes (Alcon, USA), monocular distance visual acuity improved from logMAR 0.09 ± 0.10 without correction to logMAR 0.00 ± 0.05 with best correction. De Vries et al [ 11 ] described uncorrected and best-corrected monocular visual acuity values of 0.04 ± 0.14 and −0.04 ± 0.09 after Restor +3D implantation (68 eyes) and of 0.14 ± 0.10 and −0.01 ± 0.06 after Restor +4D implantation (46 eyes), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The defocus curves of the studies by de Vries et al [ 11 ] (monocular) for Acrysof Restor +4D and +3D, by Toto et al [ 20 ] for Tecnis +4D, by Blaylock et al [ 10 ] for Acrysof Restor +4D, and Alfonso et al [ 2 ] (binocular) for Acrysof Restor + 4D, +3D, Acrilisa, all revealed a decrease in visual acuity (from logMAR 0.2 to 0.4) between −1 D and −1.5 D that we did not observe in our defocus curve. The decrease in visual acuity in the intermediate range of the defocus curve (from −1.00 to −2.00D) was no longer observed with the FineVision IOL.…”
Section: Discussionmentioning
confidence: 99%
“…Burada hastalar›n gözlük kullanma konusundaki isteksizliklerinin nedeni muhtemelen gözlüksüz ara mesafe görme seviyelerini miyopik kayman›n art›rm›fl olmas›ndan kaynaklanmaktad›r. Blayblock ve arkadafllar›n›n 15 yapt›¤› çal›flmada, ReStor implante edilen hastalara, hesaplanan G‹L de¤erinden 1 D fazla güçte lens implante edilmifl ve hastalar›n ara mesafedeki görmelerinin, yak›n ve uzak gör-meleri kadar iyi oldu¤u ölçülmüfltür.…”
Section: Tart›flmaunclassified